A Mechanically and Electrically Self‐Healing Supercapacitor. (19th February 2014) - Wang, Hua; Zhu, Bowen; Jiang, Wencao; Yang, Yun; Leow, Wan Ru; Wang, Hong; Chen, Xiaodong
<x xml:space="preserve">Abstract</x> The first mechanically and electrically self‐healing supercapacitor has been successfully fabricated. It exhibits excellent self‐healing performance with the restoration of the specific capacitance up to 85.7% of its original value even after the 5th mechanical cutting. This achievement may provide a way to expand the lifetime of future energy storage devices and endow them with desirable economic and human safety attributes, as well as promote the development of next‐generation self‐healing electronics. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>